P04.09 Development of a dendritic cell vaccine against hepatocellular carcinoma using VSV-NDV. (1st October 2020) - Gold, J; Hanesch, L; Krabbe, T; Lozano-Simon, C; Hänel, G; Rothe, M; Klopp, A; Göttert, S; Heidegger, S; Protzer, U; Subklewe, M; Altomonte, J
Abstract : Background: Activated Dendritic cells (DC ) are the immune system's allrounder: they initiate innate and adaptive immune responses; they induce instant immune reactions as well as immunologic memory. Therefore, there is growing interest in using them as a potential anticancer vaccine. 1 Here we use the beneficial immune-stimulatory properties of the novel oncolytic hybrid virus VSV-NDV to create a DC vaccine against hepatocellular carcinoma. 2 In our therapeutic approach, a sample of the patient's tumor cells is lysed in vitro with VSV-NDV (=oncolysate). The patient's DCs are then co-cultured in vitro with the oncolysate in order to activate them and load them with tumor antigens. In the end, the stimulated DCs are injected into the patient, where they can lead to a personalized and broad antitumor immune response. Materials and Methods: To investigate the potential of the approach in a cell culture system, human monocyte-derived dendritic cells were generated from PBMCs of healthy donors and incubated with VSV-NDV-lysed HepG2 hepatoma cells. Afterwards their state of activation was investigated via flow cytometry and cytokine measurement, whereas their functionality was assessed in co-culture with T-cells. In a murine system, dendritic cells were generated from bone marrow stem cells, incubated with a VSV-NDV-lysed murine HCC clone and investigated as in the human system. Results: Flow cytometry of oncolysate-stimulated DCs showed a significant upregulation of the activation markers CD86, MHC-I, MHC-II and PD-L1 (p < 0.05). Moreover, these stimulated DCs released increased amounts of cytokines. Upon co-culture of the DCs with T-cells, an elevated secretion of IFNγ by the T-cells, as well as an upregulation of T-cell activation markers could be shown, demonstrating the functional potential of the oncolysate-stimulated DCs. These results apply to both the human and the murine system. Conclusions: Our in vitro data demonstrates that the oncolysate-stimulated human and murine DCs are not only activated, but furthermore have a high functional potential. Further in vitro -experiments will be necessary to translate the process to patient-derived samples, whereas murine in vivo -experiments will give further insights into the effect of the therapeutic approach. References: Lichtenegger FS, Rothe M, Schnorfeil FM, Deiser K, Krupka C, Augsberger C, Schluter M, Neitz J, Subklewe M. Targeting LAG-3 and PD-1 to Enhance T Cell Activation by Antigen-Presenting Cells. Front Immunol 2018. Abdullahi S, Jäkel M, Behrend SJ, Steiger K, Topping G, Krabbe T, Colombo A, Sandig V, Schiergens TS, Thasler WE, Werner J, Lichtenthaler SF, Schmid RM, Ebert O, Altomonte J. A Novel Chimeric Oncolytic Virus Vector for Improved Safety and Efficacy as a Platform for the Treatment of Hepatocellular Carcinoma. J Virol 2018. Disclosure Information: J. Gold: None. L. Hanesch: None. T. Krabbe: None. C. Lozano-Simon: None. G. Hänel: None. M. Rothe: None. A. Klopp: None. S. Göttert: None. S. Heidegger: None. U. Protzer: None. M. Subklewe: None. J. Altomonte: None.